(untitled) (Research, Society and Development, 2021)
Objective: describe the practice experienced by nurses in an ambulatory surgical center, collaborating with the construction of knowledge and the improvement of transition of care at hospital discharge. Method: experience report, which refers to the performance of the authors, who perform their activities in an ambulatory surgical center of a large public university hospital located in the South of Brazil. Results: for the transition of care to be efficient, besides the patient, the companion also participates in this process, and the nurse provides guidance on specific postoperative care, the use of medications, and the return to the outpatient clinic for reevaluation with the assistant team. The patient receives a folder containing all the information about postoperative care, and the warning signs and symptoms are emphasized both in the folder and in the verbal orientation given by the nurse. Final considerations: the analysis of this study allowed us to identify the main care transition orientations for hospital discharge. By addressing the aspects of the individualized plan, the guidance on the use of medications, and the return alignments for the post-procedure consultation, it is understood that these are essential for the quality of care provided in health services.